2016
DOI: 10.1016/j.chb.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Role of social media community in strengthening trust and loyalty for a university

Abstract: As the increasing internationalization of higher education creates competition among the universities, many institutions are making use of social media communities to attract and retain students. We surveyed 215 users of the Eastern Mediterranean University (EMU) Facebook page to investigate how it influences their identification with the university community and the university brand. We further investigate how this identification influences the trust and loyalty to the institution and leads to positive behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 37 publications
1
23
0
5
Order By: Relevance
“…Adicionalmente, se verificó el registro académico de los estudiantes y se comprobó que existe una correspondencia entre los estudiantes con rendimiento más alto y los usuarios más relevantes en el uso de la aplicación, en consonancia con estudios que sugieren que hacer uso de las capacidades de colaboración a través de Facebook influye positivamente en el rendimiento estudiantil (Junco, 2015) (Nevzat et al, 2016) (Brech et al, 2016).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Adicionalmente, se verificó el registro académico de los estudiantes y se comprobó que existe una correspondencia entre los estudiantes con rendimiento más alto y los usuarios más relevantes en el uso de la aplicación, en consonancia con estudios que sugieren que hacer uso de las capacidades de colaboración a través de Facebook influye positivamente en el rendimiento estudiantil (Junco, 2015) (Nevzat et al, 2016) (Brech et al, 2016).…”
Section: Resultados Y Discusiónunclassified
“…Sin dejar de reconocer las dificultades que enfrenta, estudios recientes defienden el potencial de Facebook para desarrollar la identidad estudiantil, fidelidad y confianza en la institución universitaria por parte de los educandos y enfatizan la importancia de hacer uso de los componentes de la herramienta que influyen positivamente en el rendimiento estudiantil (Junco, 2015) (Nevzat et al, 2016) (Brech et al, 2016).…”
unclassified
“…[6][7][8] Additionally, college applicants are increasingly viewing the social media of their prospective schools and relying on information gathered via these networks to help inform their enrollment decisions. 6 A 2016 report found that half of all surveyed students were using social media for this purpose, and that about 80% took into account conversations with current students carried out through social media when making their final decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the need for further studies that can provide empirical, quantitative data to describe the exact impact of social media on marketing and recruitment efforts, student engagement, retention rates, and alumni giving, the existing literature along with anecdotal evidence and data trends strongly suggest that institutional use of social media is a prudent and valuable investment for achieving success in these initiatives. [6][7][8] Given the ubiquitous nature of social media today, simply having an online presence is unremarkable in business, and on its own, likely has no bearing on marketing and student-related…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation